Progestins in hormonal replacement therapy and contraception - Mazurek, Andrzej; Kuć, Paweł; Laudański, Tadeusz (Menopause Review/Przegląd Menopauzalny, 2003)
Progestins consist of a group of chemical substances which by different individual mechanisms exert various biological effects of progesterone. Progestins play a major role in the treatment of sterility and high-risk pregnancy and are main components of oral contraceptives (OC) and hormonal replacement therapy (HRT). The observational studies and randomized trials delivered an important insight into the side-effects of hormonal therapy. It is not only estrogen but also progestin component of oral contraception and hormonal replacement therapy which is now emphasized as a major contributory factor to cardiovascular and central nervous system as well as blood coagulation disorders and lipid and glucose metabolism malfunction. To obviate progestins side-effects risk, an individual course of hormonal therapy for each woman should be prescribed by a gynecologist. Therefore a choice of hormonal preparation, a dose of components and route of drug application should be based on the patient’s age, anamnesis and physical examination. Concomitant disorders and inherited susceptibility to some diseases should also be considered. The decision as to the hormonal therapy should be made by both a doctor and a patient.